Nexus-based water management - trade-off analysis in the Chirchik River Basin, Uzbekistan - Gafurov, Zafar; Akcakoca, Fatma; Holmatov, Bunyod; Kenjabaev, Shavkat; Umirzakov, G. (2025)
The Chirchik River Basin (ChRB) in northeastern Uzbekistan is a critical water source for urban supply, irrigated agriculture, and hydropower, yet increasing sectoral demands and variable flows intensify competition across the water–energy–food–ecosystem (WEFE) sectors. This study, conducted under the CGIAR NEXUS Policy Innovation initiative, applies a water-centric framework, combining literature review, stakeholder engagement, hydrologic modeling (SWAT), and basin hydroscheme analysis to assess trade-offs between competing uses under two different scenarios. The two scenarios are the hydropower-focused scenario and an agriculture-focused scenario. Findings reveal that irrigation remains the dominant consumer of water resources, while hydropower development and seasonal reservoir operations create constraints for agricultural reliability and ecosystem flows. Two scenario pathways illustrate contrasting pressures: a hydropower-focused trajectory enhances energy capacity but risks limiting water availability for downstream uses, while the agriculture-focused trajectory improves food production but heightens energy demand and environmental stress. Results underscore the necessity of coordinated reservoir management, explicit environmental flow allocation, and cross-sectoral planning to ensure equitable and sustainable outcomes, consistent with recent nexus assessments in Central Asia.